Current Issues in Teacher Education : History, Perspectives, and Implications. - Lassonde, Cynthia A. (Charles C Thomas Publisher, LTD, 2008)
In this edited volume by experts in the field of teacher education, Current Issues in Teacher Education combines forces from the United States and Canada to present and discuss positions on current topics and concerns in the field of teacher education. It provides an overview and multiple perspectives of issues rather than one author's position or viewpoint. This will allow the reader to reflect on multiple perspectives and to form his or her opinion and route for further action or discussion. Written in a reader-friendly style with accessible language, the book avoids the use of highly techni.